2011
DOI: 10.1016/j.amjcard.2010.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of High-Density Lipoprotein Cholesterol to Apolipoprotein A-I and A-II to Predict Coronary Calcium and the Effect of Insulin Resistance

Abstract: High-density lipoprotein (HDL) cholesterol and its apolipoproteins each capture unique lipid and cardiometabolic information important to risk quantification. It was hypothesized that metabolic factors, including insulin resistance and type 2 diabetes, would confound the association of HDL cholesterol with coronary artery calcification (CAC) and that apolipoprotein A-I (apoA-I) and/or apolipoprotein A-II (apoA-II) would add to HDL cholesterol in predicting CAC. Two community-based cross-sectional studies of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
(45 reference statements)
0
18
2
Order By: Relevance
“…After adjustment for factors that independently correlated to postprocedural cTnI, the U‐shaped association between HDL‐C/apoA‐I ratio and postprocedural cTnI elevation still existed (Figure , all P values for quadratic term were <0.05). Metabolic markers, such as diabetes, metabolic syndrome/insulin resistance, or triglycerides, may confound the link of HDL parameters to cardiovascular risk . We then additionally adjusted for diabetes, body mass index, and triglycerides in the adjusted model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After adjustment for factors that independently correlated to postprocedural cTnI, the U‐shaped association between HDL‐C/apoA‐I ratio and postprocedural cTnI elevation still existed (Figure , all P values for quadratic term were <0.05). Metabolic markers, such as diabetes, metabolic syndrome/insulin resistance, or triglycerides, may confound the link of HDL parameters to cardiovascular risk . We then additionally adjusted for diabetes, body mass index, and triglycerides in the adjusted model.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolic markers, such as diabetes, metabolic syndrome/insulin resistance, or triglycerides, may confound the link of HDL parameters to cardiovascular risk. 11 We then additionally adjusted for diabetes, body mass index, and triglycerides in the adjusted model. The relationships of HDL-C, apoA-I, and HDL-C/apoA-I ratio with myocardial injury did not change (see Supporting Information, Table S2, in the online version of this article).…”
Section: Quintiles Of Hdl-c Apoa-i and Their Ratio And Postprocedurmentioning
confidence: 99%
“…28 The inverse association between HDL 2 and CAC was limited to those with normal lipid levels. Previous reports have already suggested that HDL fails to predict CAC in dyslipemic states such as diabetes, 29 likely because lipid derangements, such as hypercholesterolemia 30 and, especially, the dyslipidemia of the metabolic syndrome, 31,32 tend to shift metabolic maturation of HDL from HDL 2 toward HDL 3 . The HDL subtype might therefore be an indicator of a highly atherogenic metabolic turnover rather than an independent predictor of coronary atherosclerosis in its own right.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma insulin levels were measured at the core laboratory of the Penn Diabetes Center by radioimmunoassay (Linco Research, St. Charles, MO). Total cholesterol (TC), TG, HDL-C, and VLDL-C were measured enzymatically, while LDL-C was measured directly, after ultracentrifugation (β-centrifugation technique) in a Centers for Disease Control (CDC) certified lipid laboratory [42] , [43] , [45] . Lp(a) and apolipoproteins were measured by immunoturbidimetric assay (Wako Chemicals, U.S.A. Inc., Richmond, VA) on a Hitachi 912 autoanalyzer (Roche Diagnostics, Basel, Switzerland).…”
Section: Methodsmentioning
confidence: 99%